1995
DOI: 10.1016/s0022-5223(95)70053-6
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of outcomes after coronary artery bypass: A randomized trial comparing intraoperative high versus low mean arterial pressure

Abstract: Higher mean arterial pressures during cardiopulmonary bypass can be achieved in a technically safe manner and effectively improve outcomes after coronary bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
214
0
6

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 404 publications
(226 citation statements)
references
References 30 publications
6
214
0
6
Order By: Relevance
“…Gold et al have shown a reduction in neurologic and cardiac morbidity when mean perfusion pressures were empirically maintained above 80mmhg. 18 This study appears to confirm that maintaining higher perfusion pressures during cardiopulmonary bypass is an adjunctive strategy to reduce organ injury and resource utilization.…”
Section: Discussionsupporting
confidence: 58%
“…Gold et al have shown a reduction in neurologic and cardiac morbidity when mean perfusion pressures were empirically maintained above 80mmhg. 18 This study appears to confirm that maintaining higher perfusion pressures during cardiopulmonary bypass is an adjunctive strategy to reduce organ injury and resource utilization.…”
Section: Discussionsupporting
confidence: 58%
“…Maximal renal blood flow on cardiopulmonary bypass is approximately 55% of prebypass flow (123). On the basis of two small studies, it seems that higher perfusion pressures may improve renal function during cardiopulmonary bypass but do not affect postoperative function (120,124). The existence of CKD as well as chronic hypertension may affect the ideal mean arterial pressure, because renal injury seems to be accompanied by a loss of autoregulation (125,126).…”
Section: Cardiopulmonary Bypassmentioning
confidence: 99%
“…It is well known that older patients and those with hypertension and diabetes may be at increased risk of hypoperfusion events owing to their lack of adequate autoregulatory mechanisms within the cerebral circulation [10]. Moreover, the ideal level of arterial blood pressure during CPB remains a debatable topic, and the few existing studies have not resulted in definitive conclusions about optimal blood pressure management [27,28].…”
Section: Commentmentioning
confidence: 99%